Platelet microaggregation in sepsis examined by quartz crystal microbalance with dissipation technology. (3rd April 2018) - Larkin, Caroline M.; Breen, Eamon P.; Tomaszewski, Krzysztof A.; Eisele, Simon; Radomski, Marek W.; Ryan, Thomas A.; Santos-Martinez, Maria-Jose
Abstract: Antiplatelet therapies remain an area of potential interest for the treatment of sepsis; however, studies of platelet aggregation in sepsis have yielded conflicting results. We examined platelet aggregation patterns in patients with septic shock using quartz crystal microbalance with dissipation technology, a microfluidic device capable of measuring platelet microaggregate formation under flow conditions. Platelet aggregation was increased in the washed platelet samples of septic patients. Conversely, these same platelets aggregated less than healthy controls when examined in their plasma.